A green chemistry approach to leather tanning process: Cage-like octa(aminosilsesquioxane) combined with Tetrakis(hydroxymethyl)phosphonium sulfate. (20th August 2019) - Gao, Dangge; Wang, Pingping; Shi, Jiabo; Li, Fan; Li, Wenbo; Lyu, Bin; Ma, Jianzhong
Abstract: The octa(aminopropylsilsesquioxane) (POSS–NH2 ) was synthesized by hydrolytic and condensation of γ-aminopropyltriethoxysilane in isopropyl alcohol solvent with tetraethylammonium hydroxide as catalyst. The structure and morphology of products was characterized by Nuclear magnetic resonance ( 1 H, 13 C-NMR), fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). A novel chrome-free tanning process based on combination tanning with cage-like octa(aminosilsesquioxane) and tetrakis(hydroxymethyl) phosphonium sulfate (THPS) has been proposed. Hygrothermal stability test showed that the shrinkage temperature ( T s ) of THPS tanned leather was obviously increased with the introduction of POSS-NH2, implying that THPS and POSS nanoparticles had synergistic effect in the combination tanning process. The tanning process is optimized as 6.0% POSS-NH2 combination with 2.5% THPS, endowing the leather with T s above 83.0 °C and thickness rate 44.6%. FT-IR analysis showed that hydrogen bond were formed between amino groups of POSS and hydroxyl groups of collagen during tanning process. The results of scanning electron microscope and energy dispersive X-ray spectroscopy (SEM-EDX) results reveal that POSS and THPS tanning agents could penetrate and bind evenly in the leather matrix, thus promoting the weaving of collagen fibers into a tight network structure. Graphical abstract: Image 1 Highlights: A new and sustainable chrome-free tanning system has been proposed. POSS-NH2 could increase the binding sites between collagen. The physical and mechanical properties of leather can be improved by POSS-THPS.